Evolution of the Use of Artificial Intelligence in Mobile Applications to Improve the Efficiency of Public Service - Judijanto, Loso; Rukmana, Arief Yanto; Fawait, Aldi Bastiatul; Rahmah, Sitti; Sugiarto, Sugiarto (Westscience Press, 2024)
The integration of artificial intelligence (AI) into mobile applications has transformed public service delivery by enhancing efficiency, accessibility, and responsiveness. This study employs a bibliometric approach to analyze the evolution of AI applications in public service, focusing on research trends, key contributors, and thematic developments from 2000 to 2024. The findings reveal a rapid increase in research output since 2018, driven by advancements in enabling technologies such as IoT, 5G, and machine learning, as well as global challenges like the COVID-19 pandemic. Key application areas identified include healthcare, smart cities, and governance, with AI-powered mobile apps demonstrating significant potential in addressing societal needs. However, challenges related to data privacy, algorithmic bias, and technical infrastructure persist. This study underscores the importance of ethical frameworks, interdisciplinary collaboration, and localized solutions to maximize the impact of AI in public service delivery. The findings offer valuable insights for researchers, practitioners, and policymakers seeking to leverage AI for smarter and more equitable public services.